2020
DOI: 10.7759/cureus.9410
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series on Uterine Arteriovenous Malformations: A Life-Threatening Emergency in Young Women

Abstract: Uterine arteriovenous malformation (AVM) is a rare condition, with few cases reported in the literature. Despite being rare, it is a potentially life-threatening condition in women of childbearing age. It should be considered in the differential diagnosis of prolonged or irregular vaginal bleeding, which, otherwise, can lead to critical complications ending up in severe morbidity and mortality. This case series describes four cases of young Asian women aged between 33 and 38 years who presented with irregular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…Uterine AVMs were first reported in 1926 [ 1 , 4 ]. These are rare entities with an unknown prevalence, with less than 100 cases documented in the literature [ 4 - 5 ]. An AVM of the uterus is most commonly a fistulous connection between the branches of the uterine artery and the myometrial venous plexus, which bypasses the normal intervening capillary network [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uterine AVMs were first reported in 1926 [ 1 , 4 ]. These are rare entities with an unknown prevalence, with less than 100 cases documented in the literature [ 4 - 5 ]. An AVM of the uterus is most commonly a fistulous connection between the branches of the uterine artery and the myometrial venous plexus, which bypasses the normal intervening capillary network [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The conservative approach, including hormonal medications, i.e., combined hormonal contraceptives 12,13 , progesterone, Gonadotropinreleasing hormone agonist (GNRHa4) 14,15 , danazol and methylergonovine maleate 16 are feasible for hemodynamically stable patients with mild or irregular vaginal bleeding. Literature review revealed many case reports supporting the successful use of hormonal agents in regression of AVM [12][13][14][15][16] . Downregulation of estrogen secretion increased uterine arterial resistance and decreased uterine blood flow is postulated as the possible mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…The radiological features are summarized in Table 1. 2,19,25,[54][55][56][57][58][59][60][61][62] Table 1. Common Imaging Findings of Uterine Arteriovenous Malformation (UAVM).…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…Common Imaging Findings of Uterine Arteriovenous Malformation (UAVM). 2,19,25,[54][55][56][57][58][59][60][61][62]…”
Section: Diagnostic Imagingmentioning
confidence: 99%
See 1 more Smart Citation